Peran Branding dan Packaging terhadap Peningkatan Daya Tarik Produk Lokal : Studi Kuantitatif pada UMKM Kerupuk Cikur Silawas - Anisa Putri Maharani; Rina Madyasari; Alfin Nur Arifah; Ardhiansyah Ardhiansyah (Pusat Riset dan Inovasi Nasional, 2026)
Competition in the Micro, Small, and Medium Enterprises (MSMEs) sector is becoming increasingly intense, requiring business owners to enhance product attractiveness in order to remain competitive in the market. One strategy that can be implemented is strengthening branding and improving packaging to build a strong product identity while attracting consumers' attention. This study aims to examine the influence of branding and packaging on product attractiveness at Kerupuk Cikur Silawas MSME. This study employed a quantitative approach with a causal research design. The population consisted of consumers who had seen or purchased Kerupuk Cikur Silawas products in Tasikmalaya Regency. A total of 100 respondents were selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The findings indicate that branding has a positive and significant effect on product attractiveness, with a t-value of 4.726 and a significance level of 0.000. Packaging also has a positive and significant effect on product attractiveness, with a t-value of 4.667 and a significance level of 0.000. The Adjusted R Square value of 0.568 indicates that branding and packaging explain 56.8% of the variation in product attractiveness, while the remaining 43.2% is influenced by other factors not included in the research model. These findings suggest that strengthening branding and improving packaging can enhance product attractiveness. Therefore, both aspects should receive greater attention from MSMEs owners as strategic efforts to improve product competitiveness in the market.